What happened on Blackstone Avenue? Transaction costs, scholarly midwives, and the birth of the Coase theorem - Steven G. Medema (Duke University, Center for the History of Political Economy (CHOPE), 2024)
The Coase theorem has been shrouded in ambiguity and confusion throughout its life, this despite the prominent role that it plays in economic and legal analysis. As this paper demonstrates, this is no less true of the path by which Coase came to the result that bears his name. Drawing on published and archival sources, we discuss the challenges that Coase encountered in formulating his argument and illuminate the roles of other scholars in correcting Coase's errors-particularly as regards the impact of transaction costs on his negotiation analysis-and nudging him toward a theoretically valid result. We also show that Coase's legendary 'conversion' of the disbelieving Chicago economists was both less extensive than commonly believed and likely involved a their acceptance of a result that is both demonstrably incorrect and fundamentally different from that which Coase published in "The Problem of Social Cost." All of this works to highlight the ongoing challenges posed by transaction costs for understanding the domain and range of the Coase theorem, challenges that are as old as the theorem itself.
Keywords: K00; H2; D62; B2; 330; Coase theorem; Ronald Coase; externalities; market failure; transaction costs